High-temperature resistant broadband infrared stealth metamaterial absorber. (December 2022) - Quan, Cong; Zou, Jinglan; Guo, Chucai; Xu, Wei; Zhu, Zhihong; Zhang, Jianfa
Abstract: In this paper, we propose a broadband infrared stealth metamaterial absorber based on an improved metal-dielectric-metal structure where its top pattern consists of multi-layers. The structure uses high-temperature resistant materials instead of traditional low melting point precious metals and achieves selective thermal radiation in the infrared band. The study shows that with the increase of the number of layers, the absorption peak and bandwidth of the non-atmospheric window band expands. When the thickness of the structure is five layers, it can match well with the atmospheric absorption spectra. The polarization sensitivity and infrared stealth performance at different temperatures of the structure with five-layer are studied in detail. Compared with black body, the selective thermal emitter maintains radiation reduction rates greater than 80% in MWIR and LWIR regions. The high temperature resistant heat emitter proposed by us can be used in spectrally selective thermal radiation, thermal management and thermal camouflage, which has a very promising application prospect.